2022
DOI: 10.1096/fasebj.2022.36.s1.r6073
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the endocrine response to macronutrients in the context of a ketogenic diet

Abstract: A ketogenic diet (KD) consists of long‐term carbohydrate avoidance and the resulting elevation in ketones due to low insulin. This altered energetic state may result in unique hormonal responses to macronutrients. Accordingly, the purpose of this study was to quantify the endocrine response to various macronutrients in the context of a KD. Nine subjects (6 male, 3 female) who adhere to a carbohydrate‐restricted diet (50g or less carbohydrates per day) completed three interventions, each at least one week apart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In this context, the results of a very recent meta-analysis on the use of protein intake to support muscle mass and function in healthy adults showed that there was not a significant difference when performing the analysis of subgroups by age [ 47 ]. However, it is tempting to speculate that the low insulin-to-glucagon ratio induced by the severe restriction in carbohydrates intake during the active phase of the VLCKD could be associated with multiple changes in endocrine axes involved in the regulation of body composition [ 38 , 48 , 49 , 50 ], including the somatotropic axis [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the results of a very recent meta-analysis on the use of protein intake to support muscle mass and function in healthy adults showed that there was not a significant difference when performing the analysis of subgroups by age [ 47 ]. However, it is tempting to speculate that the low insulin-to-glucagon ratio induced by the severe restriction in carbohydrates intake during the active phase of the VLCKD could be associated with multiple changes in endocrine axes involved in the regulation of body composition [ 38 , 48 , 49 , 50 ], including the somatotropic axis [ 51 ].…”
Section: Discussionmentioning
confidence: 99%